The Use of the Robust GREG Estimator to Estimate Small Trade Firms - Grażyna Dehnel (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
In the face of dynamic changes in the economy, there is a growing demand for multivariate statistics for cross‑classified domains. In economic statistics, this demand poses a particular challenge owing to the unique character of the population of enterprises, which is what motivates the search for estimation methods that can exploit administrative sources to a greater extent. The adoption of new solutions in this area is expected to increase the scope of statistical outputs and improve the efficiency of estimates. The purpose of the presented study is to test the application of the robust GREG estimator based on the LS method and least median of squares regression to estimate characteristics of small trade firms operating in 2012. The estimation process is supported with delayed variables from administrative registers used as auxiliary variables. The paper refers to small area estimation methods. The variables of interest are estimated at the low level of aggregation represented by cross‑section province and NUTS 2.